Brazilian red propolis synergistically with imipenem modulates immunological parameters and the bactericidal activity of human monocytes against methicillin-resistant Staphylococcus aureus (MRSA) - Ripari, Nicolas [UNESP]; Honorio, Mariana da Silva [UNESP]; Sartori, Arthur Alves [UNESP]; Oliveira, Larissa Ragozo Cardoso de [UNESP]; Bastos, Jairo Kenupp; Sforcin, Jose Mauricio [UNESP] (Oxford Univ Press, 2024)
Objectives: Propolis is a bee product found all over the globe and has a well-known antibacterial activity. Previous findings of our group revealed that the combination of Brazilian red propolis (BRP) with a lower concentration of imipenem (IPM) exerted a bactericidal action against methicillin-resistant Staphylococcus aureus (MRSA) in vitro. Here, we aimed at investigating the effects of BRP in combination or not with IPM on human monocytes to assess a possible immunomodulatory action. Methods: Monocyte metabolic activity was analysed by MTT assay, cytokine production (TNF-alpha, IL-1 beta, IL-6, IL-8, and IL-10) by ELISA, and the expression of cell markers (TLR-2, TLR-4, HLA-DR, and CD80) by flow cytometry. The bactericidal activity of monocytes over MRSA was determined by colony-forming units' count. Key findings: BRP alone or in combination with IPM exerted no cytotoxic effects on monocytes. BRP downregulated TLR-2 expression and inhibited TNF-alpha, IL-1 beta, and IL-6 production, while BRP + IPM stimulated these parameters. BPR alone or in combination increased the bactericidal activity similarly to LPS-activated monocytes. Conclusions: Data indicated the potential of BRP as an anti-inflammatory agent increasing the bactericidal activity of monocytes against MRSA. The combination of BRP + IPM exhibited a stimulatory profile that may be potentially useful in treating patients with MRSA infection.
Keywords: propolis; monocyte; Toll-like receptor; cytokine; methicillin-resistant Staphylococcus aureus